التدخل السوري في لبنان وإشكالیة العلاقة السوریة – اللبنانیة (Journal of the College of Education for Women, 2019)
The relation ship between Syria and Lebanon is a distinguished onebecause of the cultural social geographic and historical common factors. Sothat, Syria considers that Lebanon has a stratieyical depth for it, especially itsconflict with (Israel) does end and parts of its lands still under the occupationof the Zionist thus, any conflict in Lebanon between parties and ethnicsgroups could be considered an important influence on the bases of the Syrianpolicy. Moreover the issue of Palestine which is considered the central issuefor Syria and Arab as whole. In addition to some of the political movementsthat happened in the region itself. It could be said that Syrian interference inLebanon has a positive influence, despite the negative one, it lies inprotecting them from being killed on the bases of identity. This helps inreducing the domination of some armed groups. But the point view of theSyrian differs from that of the Lebanese groups, so that Syrian interferencelost its validity and thus it should be ended, as a result of the internationaldecision 1559 which demanded Syria to leave Lebanon after securitysettlement.